THE EFFECT OF PROFITABILITY, CREDIT RISK AND BOARD OF DIRECTOR ON INVESTOR TRUST WITH COMPANY SIZE AS MODERATION - Trisandi Eka Putri; Icih Icih; Qurrota Ayuni (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
This study aims to determine the factors that influence investor confidence in Indonesian banking. The data used in this study were obtained from the financial statements of banking companies published in 2016-2020. This study hypothesizes profitability, credit risk, independent board of commissioners as independent variables and investor confidence as the dependent variable and firm size as a moderating variable. This research is located on the Indonesia Stock Exchange (IDX). The sampling method used purposive sampling technique. Research data obtained through non-participant observation method with secondary data collection. Analysis of research data using multiple linear regression with SPSS application. The results of this study indicate that profitability has a positive effect on investor confidence, credit risk has a negative effect on investor confidence, the independent board of commissioners has a negative effect on investor confidence. Simultaneously all independent variables have a significant effect on the dependent variable.